2011
DOI: 10.1111/j.1552-6569.2011.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Cerebral Aneurysms at a Low‐Volume Community Hospital Practice: Management Strategies, Complications, and Outcomes

Abstract: Endovascular coil embolization at a small volume nonspecialized community center is feasible with satisfactory procedural risk and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although these technologies are becoming more available, studies have historically indicated a relationship between health outcomes and patient volumes after both surgical and endovascular repair of aneurysms 3–7 justifying critical review of the outcomes and complication rates, especially at the nonspecialized low‐volume institutions. In this issue of Journal of Neuroimaging , Gordhan and colleagues 8 present their experience in endovascular treatment of cerebral aneurysms at a low‐volume community hospital, specifically addressing its safety and efficacy. This is the first such evaluation from a US‐based center complimenting previously published studies on good outcomes of aneurysm clipping at low‐volume centers 9,10 .…”
mentioning
confidence: 99%
“…Although these technologies are becoming more available, studies have historically indicated a relationship between health outcomes and patient volumes after both surgical and endovascular repair of aneurysms 3–7 justifying critical review of the outcomes and complication rates, especially at the nonspecialized low‐volume institutions. In this issue of Journal of Neuroimaging , Gordhan and colleagues 8 present their experience in endovascular treatment of cerebral aneurysms at a low‐volume community hospital, specifically addressing its safety and efficacy. This is the first such evaluation from a US‐based center complimenting previously published studies on good outcomes of aneurysm clipping at low‐volume centers 9,10 .…”
mentioning
confidence: 99%